Exploring the horse-human relationship - Clough, H.G.R. (2019)
From a vital role in agriculture, food production and transportation, equids are now used primarily for sporting and leisure ventures, and often as much-loved companions. However, changing human demands have not only shaped the horse into the modern day animal we see today, but altered the way in which humans interact with equids on both a personal and professional level. Scientific research around human-animal relationships and bonds has increased exponentially, but there remains a paucity of research on the relationship between horse and human. The aim of this project is to explore that relationship. With no comprehensive reviews consolidating the current state of evidence, a scoping review was performed first. Twenty-three publications met final inclusion criteria, found to be diverse, heterogeneous and lacking a robust evidence-base. Due to the heterogeneity of the studies, very limited comparisons of aims, objectives and methodologies could be drawn. Nonetheless, several different areas of research were identified; equine training methodologies and behaviour, horses within sport and leisure, and equine behaviour and reactions towards humans. Significant gaps within the evidence were documented, including how the relationship between horse and owner affects decisions made throughout the horse’s life. A mixed methods approach using in-depth interviews and cross-sectional questionnaires was used to explore this area of the horse-human relationship. Owners with previous experience of both purchasing a horse and making euthanasia decisions, were recruited through an online questionnaire exploring characteristics of people involved with the care of horses. Owner typing was performed based on responses to statements exploring the relationship participants had with their horses. This identified potential interviewees with a range of experiences and relationships with their horses. In-depth interviews allowed for further exploration of these personal attachments for eleven participants, and a deeper understanding of the motivations and experiences owners have surrounding purchasing and euthanasia decisions for horses. The importance of the horse as a pet (85% of participants strongly agree or agree) and family member (92.9% of participants strongly agree or agree), irrespective of owner experience and requirements, was highlighted in both online survey respondents and interview candidates. Expectations and obligations, as well as the conflict between them were key emerging themes for the purchasing decisions made by interview participants. Furthermore, the practical, obligational, and personal aspects of euthanasia decision-making, and the need for support was analogous across the interview owner groups. The emotional impact euthanasia had on the owners and their responsibility grief, highlights the extent to which an important decision such as euthanasia has on an owner, particularly for those with less experience. The data highlighted the need to support owners when making such decisions, taking into account their strong attachments which may impact their judgement when a decision needs to be made. Themes and ideas identified from these interviews were tested within a larger population of horse owners through a cross-sectional survey of owners with experience of purchase and euthanasia. Results from 495 survey respondents identified high confidence, with the majority of owners (47.0%) ranking themselves a 10 with regards to their confidence in providing daily care to their own, and other people’s horses. The majority of participants were very confident when making several decisions surrounding the purchase of their most recent horse; 58.9% very confident in deciding what horse to view and 52.3% very confident trying the horse and deciding if it was suitable. One in four less experienced participants did not seek any advice on the suitability of the horse, and the majority of participants sought no advice on the type of horse to view (39.2%) and its cost (49.9%). The most important requirements when purchasing a horse were: temperament when ridden (67.8%) and handled (70.5%), and conformation (43.2%). The most frequent consideration when purchasing a horse was the ability of the horse to carry out its desired function (76.9%). There were 409 participants with experience of euthanasia, and the majority of the participants’ described this as humane destruction (59.2%). The horse’s quality of life at the time of euthanasia (95.8%) or in the future (88.6%) were very important factors for participants during the euthanasia decision. Advice was sought from the vet by most participants (94.7%), highlighting the importance of shared decision making between the client and vet. Participants most frequently ‘agreed’ or ‘strongly agreed’ that they would make the same decision again (98.1%), and were confident it was the right decision for the horse (95.6%). This suggests that participants did not regret the decision they made for their horses, but with a high percentage described as ‘humane destructions’, this raises the question of whether these decisions were made too late. This research has identified key factors of the horse-human relationship that were important in decision-making around purchase and euthanasia. Recommendations for future work include the validation of owner-typing and horse suitability tools for purchase, and the development of resources and support networks to draw on when considering euthanasia.